High Energy, Optical, and Infrared Detectors for Astronomy V 2012
DOI: 10.1117/12.926323
|View full text |Cite
|
Sign up to set email alerts
|

Charge-coupled devices for the ESA Euclid M-class Mission

Abstract: The European Space Agency has funded e2v's development of an image sensor for the visible instrument in the Euclid space telescope. Euclid has been selected for a medium class mission launch opportunity in 2020. The project aims to map the dark universe with two complementary methods; a galaxy red-shift survey and weak gravitational lensing using near infrared and visible instruments. The baseline for the visible instrument was to be the CCD203-82, which has been successfully flown on NASA's Solar Dynamics Obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 2 publications
(1 reference statement)
0
24
0
Order By: Relevance
“…VIS comprises an array of thirty six CCD273s manufactured by e2v technologies, with a broad red bandpass (550 nm to 900 nm) and arranged in a 6x6 matrix on the front of the focal plane array [2][3] [4]. The impact on charge transfer efficiency (CTE) due to proton irradiation on the CCD273 and similar e2v devices (CCD204) has been subject to detailed investigations [5] [6] and has concluded that under normal operating conditions, the CCD273 satisfies mission requirements within the tolerances placed on the specification.…”
Section: Introductionmentioning
confidence: 99%
“…VIS comprises an array of thirty six CCD273s manufactured by e2v technologies, with a broad red bandpass (550 nm to 900 nm) and arranged in a 6x6 matrix on the front of the focal plane array [2][3] [4]. The impact on charge transfer efficiency (CTE) due to proton irradiation on the CCD273 and similar e2v devices (CCD204) has been subject to detailed investigations [5] [6] and has concluded that under normal operating conditions, the CCD273 satisfies mission requirements within the tolerances placed on the specification.…”
Section: Introductionmentioning
confidence: 99%
“…It is a 4k × 1k device with 12 m square pixels, utilising a split register with two output nodes each of which can be operated using an amplifier responsivity of 4.5 µV/h + or 1.5 µV/h + . It is based on the same architecture used in the CCD203, previously flown on board the Solar Dynamics Observatory launched in 2010 18 , but with the inclusion of a charge injection structure. Both p-channel 7,19 and n-channel 20 variants have been produced.…”
Section: Ccd204mentioning
confidence: 99%
“…The study described in this paper is being performed as part of a European Space Agency (ESA) funded investigation into the performance benefits provided through the use of a p-channel rather than an n-channel CCD 18 . The study used seven e2v technologies p-channel CCD204 5 devices fabricated with exactly the same process as standard n-channel CCDs but with simple reversal of dopant polarities, the gate dielectric is the same in both cases.…”
Section: Introductionmentioning
confidence: 99%
“…Niemi et al [11] measured, with uncertainties of 3s, the PRF of one version of the CCD-273 using the spot projection. The CCD-273 is the device that will populate the visible channel of the Euclid payload [12]. Niemi et al estimated the CCD PRF by fitting the data to a model using a Bayesian approach.…”
Section: B Overview Of the Measurement Techniquesmentioning
confidence: 99%